MRI-compatible bone phantom for evaluating ultrasonic thermal exposures - Menikou, Georgios; Yiannakou, Marinos; Yiallouras, Christos; Ioannides, Cleanthis; Damianou, Christakis A. (My University, 2016)
Objective The goal of the proposed study was the development of a magnetic resonance imaging (MRI) compatible bone phantom suitable for evaluating focused ultrasound protocols. Materials and methods High resolution CT images were used to segment femur bone. The segmented model was manufactured with (Acrylonitrile Butadiene Styrene) ABS plastic using a 3-D printer. The surrounding skeletal muscle tissue was mimicked using an agar-silica-evaporated milk gel (2% w/v-2% w/v-40% v/v). MR thermometry was used to evaluate the exposures of the bone phantom to focused ultrasound. Results The estimated agar-silica-evaporated milk gel's T1 and T2 relaxation times in a 1.5 T magnetic field were 776 ms and 66 ms respectively. MR thermometry maps indicated increased temperature adjacent to the bone, which was also shown in situations of real bone/tissue interfaces. Conclusion Due to growing interest of using MRI guided Focused Ultrasound Surgery (MRgFUS) in palliating bone cancer patients at terminal stages of the disease, the proposed bone phantom can be utilized as a very useful tool for evaluating ultrasonic protocols, thus minimizing the need for animal models. The estimated temperature measured and its distribution near the bone phantom/agar interface which was similar to temperatures recorded in real bone ablation with FUS, confirmed the phantom's functionality.
Keywords: Bone; Cancer; MRI; Ultrasound